2019
DOI: 10.1016/j.aap.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the safety impact of connected and autonomous vehicles on motorways

Abstract: Recent technological advancements bring the Connected and Autonomous Vehicles (CAVs) era closer to reality. CAVs have the potential to vastly improve road safety by taking the human 3 driver out of the driving task. However, the evaluation of their safety impacts has been a major challenge due to the lack of real-world CAV exposure data. Studies that attempt to simulate CAVs by using either a single or integrating multiple simulation platforms have limitations, and in most cases, consider a small element of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(184 citation statements)
references
References 19 publications
7
131
0
1
Order By: Relevance
“…On the contrary, Rahman and Abdel-Aty [27] applied surrogate safety measures to evaluate the safety impact of exclusive lanes for CAVs. Besides, other research studies on the safety impacts of CAVs applied surrogate safety measures [28,29] presented the feasibility of this kind of evaluation. Details of aforementioned literatures are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, Rahman and Abdel-Aty [27] applied surrogate safety measures to evaluate the safety impact of exclusive lanes for CAVs. Besides, other research studies on the safety impacts of CAVs applied surrogate safety measures [28,29] presented the feasibility of this kind of evaluation. Details of aforementioned literatures are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The safety of the heterogeneous flow has been studied as well. Papadoulis et al (2019) assessed the safety benefit of CAV and found 12-47% reduction in traffic conflict at 25% MPR. Local coordination among CAV was implemented with a threshold of 0.6 s form the vehicle upstream and downstream in the target lane.…”
Section: Relevant Researchmentioning
confidence: 99%
“…Besides, the increase of road capacity indicates a smaller average headway, which may bring safety issues. To deal with this, studies were carried out to find a balance between increases of traffic capacity and accident risks [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%